Host immune responses to antigens derived from a predominant strain of Mycobacterium tuberculosis. Issue 1 (July 2016) - Hur, Yun-Gyoung; Chung, Wou Young; Kim, Ahreum; Kim, Young Sun; Kim, Hyon-Suk; Jang, Sun-Hee; Kim, Yeun; Lee, Hyeyoung; Park, Kwang Joo; Cho, Sang-Nae
Summary: Objectives: Beijing strain of Mycobacterium tuberculosis (M. tb) is characterized by a high incidence of transmission, relapse, and drug resistance. This study aimed to determine host immune responses to antigens derived from the Beijing/K strain which has been highly prevalent in tuberculosis (TB) outbreaks in South Korea. Methods: We recruited 52 TB patients and 96 healthy subjects comprising 31 individuals with latent TB infection (LTBI) and 65 TB-naïve controls based on QuantiFERON-TB Gold In-Tube (QFT-IT) tests. Blood samples were obtained for diluted whole-blood assays, multiplex bead arrays, ELISpot assays, and HLA typing. Molecular genotyping of M. tb was performed using clinical isolates. Results: Active TB and LTBI groups were differentiated by TNF-α concentrations induced by the Beijing/K strain-derived antigens, MTBK_24790 and MTBK_24800 (P < 0.001). MTBK_24800-induced IFN-γ and CXCL10 concentrations discriminated the TB-infected groups from TB-naïve controls (P < 0.001). IFN-γ-producing T cells were generated in 87.2% of TB patients in response to MTBK_24800 peptide antigens. The major immunogenic epitope was at C-terminal of the antigen, and predominantly recognized by HLA-DR4 and -DQ4. Conclusions: Measurement of IFN-γ, CXCL10, and TNF-α concentrations induced by MTBK_24790 and MTBK_24800 may contribute to improved diagnosis of TB and vaccine development in regions where the Beijing/K strain is endemic. Highlights: Beijing/K strains of M. tb are highly transmissible and predominant in South Korea. MTBK_24790 and MTBK_24800 were identified from Beijing/K strains of M. tb . Active TB and LTBI were differentiated by the Beijing/K antigen-induced TNF-α. M. tb infection was detected by the MTBK_24800-induced IFN-γ and CXCL10. Beijing/K antigen-specific IFN-γ, CXCL10, and TNF-α may help the IGRA performance.